Integration of Repository System in Optimization Data for Graduates’ Scientific Paper - Opik Taupik Kurahman; Sopia Respiawati; Agus Sulaeman; Nur Lukman (Program Studi Ilmu Perpustakaan UIN Alauddin, 2022)
Academic libraries manage collections and offer the community the best services possible, one of which is library-free services. In the free management of a library, an institutional repository is an essential aspect because, with it, graduates can publish their writings to the public. However, the number of graduates and repository data from various universities differ. It requires integration, automation, and graduation registration systems, so everything is interrelated. As a result, everything is interconnected and cannot proceed if the first stage is not completed. So it is necessary to create an online library free submission system that can combine these three systems. The study shows that the three systems can be integrated, providing maximum data optimization between graduate and repository data.